ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT VISI TELEKOMUNIKASI INFRASTRUKTUR TBK - Aryudha Ramadhan Ardyanto; Sri Murwanti (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the comparison of financial performance before and after the acquisition at Pt Visi Telekomunikasi Infrastruktur Tbk. This research method is quantitative. The population of this study is all time series data (time series data) of the company's financial statements of PT Visi Telekomunikasi Infrastruktur Tbk. The sample in this study is the company's financial statements of PT Visi Telekomunikasi Infrastruktur Tbk three years before the acquisition (2016-2018) and three years after the acquisition (2019-2021). The data used is secondary data. The data collection method in this study used documentation methods. This analysis technique is carried out with parametric difference tests or non-parametric difference tests and normality tests. Data from this study will be processed using SPSS software. The result of this study is the Current Ratio (CR) shows that there is a difference before and after the acquisition of PT Visi Telekomunikasi Infrastruktur Tbk. There is a difference in the Return on Asset (ROA) ratio before and after the acquisition at PT Visi Telekomunikasi Infrastruktur Tbk. There is a difference in Debt to Equity Ratio (DER) before and after the acquisition at PT Visi Telekomunikasi Infrastruktur Tbk. The results of this study Net Profit Margin (NPM) shows that there is a difference before and after the acquisition at PT Visi Telekomunikasi Infrastruktur Tbk. The results show that there is a difference in the ratio of Total Asset Turn Over (TATO) before and after the acquisition at PT Visi Telekomunikasi Infrastruktur Tbk